Feasibility of Applying Case Law of Ad Hoc International Tribunal for Former Yugoslavia in Cases of Sexual offences committed by Coercion - Gabaraev, Ioseb (Journal of Law, 2019)
The effective functioning of mechanism of the national human rights protection implies approximation of national legislation towards international standards and refining the practice of national courts, which should be a continuous process and be aimed at adapting best international judicial practice to national judicial practice. In order to ensure adherence to high standards of universally recognised human rights it is essential and thus decisive significance is assigned to share practice of various countries and international institutions. In the present article, discussing the stages of the evolutionary development of the definition of rape and distinguishing it from the crime of torture is based on analysis of landmark decision of the ad hoc International Criminal Tribunal for the former Yugoslavia (hereinafter referred as ICTY) the purpose of which is to introduce and apply them in judicial practice and thus to improve the reasoning of the decisions of national courts in similar cases.